Correction to: Complementary and alternative medicine for treatment of atopic eczema in children under 14 years old: a systematic review and meta-analysis of randomized controlled trials - Chun-li Lu; Xue-han Liu; Trine Stub; Agnete E. Kristoffersen; Shi-bing Liang; Xiao Wang; Xue Bai; Arne Johan Norheim; Frauke Musial; Terje Alræk; Vinjar Fonnebo; Jian-ping Liu (BMC, 2019)
ᅟ